Non-aqueous electrolyte and lithium ion battery containing same
By adding cyclic carbonic acid-sulfate and amphoteric salt structure additives to the nonaqueous electrolyte of lithium-ion batteries, the problem of capacity attenuation of lithium-ion batteries at high temperatures is solved, and more stable battery performance and extended cycle life are achieved. .
Patent Information
- Application Number
- CN202411615591.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The capacity of lithium-ion batteries rapidly attenuates under high temperature conditions, mainly due to the oxidation and decomposition of the electrolyte on the positive electrode surface and the accelerated side reaction of the positive electrode interface, resulting in the fragmentation of the positive electrode material and the increase in internal resistance.
A nonaqueous electrolyte solution is used, which contains compound A with a cyclic carbonic acid-sulfate structure and compound B with an amphoteric salt structure as additives. These additives reduce the fragmentation of the positive electrode material and the side reaction of the electrolyte by adjusting the solvation structure of the lithium ions and forming protective long-chain organic oligomers.
Effectively build a relatively stable CEI film, reduce internal resistance growth, improve the high-temperature storage performance of lithium-ion batteries, and extend its cycle life.
Smart Images

Figure CN119481268A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a non-aqueous electrolyte and a lithium ion battery containing the non-aqueous electrolyte. Background Art
[0002] Lithium-ion batteries have been used in many fields to demonstrate their advantages of high energy density, light weight, and long cycle life, from small digital devices to electric vehicles, but the disadvantage of low application scenarios of lithium-ion batteries at high temperatures limits the further expansion of lithium-ion battery applications. Due to high temperature conditions, the oxidation and decomposition of the electrolyte on the positive electrode surface is accelerated, and the side reactions at the positive electrode interface are accelerated, resulting in the fragmentation of the positive electrode material and the increase of the battery's internal resistance, causing the rapid decay of the lithium-ion battery capacity at high temperatures. Therefore, constructing a stable CEI film, reducing the side reactions of the electrolyte at the positive electrode interface, and reducing the internal resistance growth of lithium-ion batteries at high temperatures is an effective way to expand the application scenarios of lithium-ion batteries.
[0003] Therefore, a non-aqueous electrolyte and a lithium ion battery containing the non-aqueous electrolyte are urgently needed to solve the above problems. Summary of the invention
[0004] The object of the present invention is to provide a non-aqueous electrolyte and a lithium ion battery comprising the non-aqueous electrolyte. The non-aqueous electrolyte comprises a compound A having a cyclic carbonate-sulfate structure and a compound B having an amphoteric salt structure as additive compounds. The non-aqueous electrolyte comprising the additive compounds is applied to a lithium ion battery to construct a relatively stable CEI film, reduce internal resistance growth, and improve the high-temperature storage performance of the lithium ion battery.
[0005] To achieve the above object, the present invention provides a non-aqueous electrolyte, comprising a lithium salt, a non-aqueous organic solvent and an additive, wherein the additive comprises a compound A having a structure shown in Formula 1 and a compound B having a structure shown in Formula 2:
[0006]
[0007] Wherein, m and p are each independently selected from 0 or 1, X, Y, and Z are each independently selected from C or S, and X, Y, and Z are not C or S at the same time, R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, and n is a natural number of 1 to 5.
[0008] Compared with the prior art, the non-aqueous electrolyte of the present invention includes a compound A containing a cyclic carbonate-sulfate ester as shown in formula 1 and a compound B containing an amphoteric salt as shown in formula 2. Compound A and compound B are used together as additives. First, the solvation structure of lithium ions in the lithium ion battery can be adjusted by the amphoteric salt structure of compound B to promote the transmission of lithium ions in the battery. At the same time, compound A undergoes an oxidation-reduction reaction in the positive and negative electrodes, and can form a relatively long-chain organic oligomer in which S=O and C=O cross during the cycle of the lithium ion battery. The organic oligomer covers the surface of the positive and negative electrode materials and wraps the inorganic SEI components inside the SEI layer, thereby preventing the rigid inorganic components from breaking during the charge and discharge cycle of the lithium ion battery, causing the electrolyte to penetrate into the electrode, causing the electrolyte to decompose and fail, and helping to protect the positive and negative electrodes, slowing down the side reactions between them and the electrolyte at high temperature, slowing down the fragmentation and pulverization of the positive electrode material particles, and reducing the internal resistance growth. At the same time, the inorganic components such as lithium carbonate and lithium sulfate in the reduction product also help the transmission of lithium ions, thereby improving the high-temperature cycle performance of the battery. Therefore, by using compound A and compound B as the additive in the non-aqueous electrolyte of lithium-ion batteries, a more stable CEI film can be constructed, internal resistance growth can be reduced, and high-temperature cycle performance of lithium-ion batteries can be improved.
[0009] Furthermore, in the present invention, X, Y, and Z are selected from C, one of m and p is 0 and the other is 1, X, Y, and Z are selected from S, one of m and p is 0 or 1 and the other is 1, R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, and n is a natural number of 1-5.
[0010] Furthermore, the compound A of the present invention is at least one selected from compounds 1 to 4:
[0011]
[0012] Specifically, the preparation method of compound 4 can be as follows: mannitol, dimethyl carbonate and methanol are mixed, and then catalysts triethylamine and N,N-dimethylformamide are added, and intermediate 1 is obtained by heating reaction; intermediate 1 is heated to react with thionyl chloride to obtain intermediate 2; intermediate 2 is oxidized by an oxidant such as periodic acid to obtain compound 4, and the yield is 70%. The preparation route of compound 4 is shown in reaction formula 1.
[0013]
[0014] The preparation method of compound 1 can be as follows: heating mannitol and thionyl chloride to react to obtain intermediate 3; mixing intermediate 3, dimethyl carbonate and methanol, and then adding catalysts triethylamine and N,N-dimethylformamide to react to obtain intermediate 4; oxidizing intermediate 4 with an oxidant such as periodic acid, and then purifying it by column chromatography to obtain compound 1, with a yield of 60%. The preparation route of compound 1 is shown in reaction formula 2.
[0015]
[0016]
[0017] The preparation method of compound 2 is similar to that of compound 1, specifically, mannitol and thionyl chloride are heated to react to obtain intermediate 5; intermediate 5, dimethyl carbonate and methanol are mixed, and then catalysts triethylamine and N,N-dimethylformamide are added to react to obtain intermediate 6; intermediate 6 is oxidized by an oxidant such as periodic acid and then purified by column chromatography to obtain compound 2, with a yield of 20%. The preparation route of compound 2 is shown in reaction formula 3.
[0018]
[0019] The preparation method of compound 3 is similar to that of compound 4. Specifically, mannitol, dimethyl carbonate and methanol are mixed, and then catalysts triethylamine and N,N-dimethylformamide are added, and the intermediate 7 is obtained by heating reaction; intermediate 7 is heated to react with thionyl chloride to obtain intermediate 8; intermediate 8 is oxidized by an oxidant such as periodic acid and then purified by column chromatography to obtain compound 3 with a yield of 20%. The preparation route of compound 3 is shown in reaction formula 4.
[0020]
[0021] Furthermore, the compound B of the present invention is at least one selected from compounds 5 to 7:
[0022]
[0023] Further, the mass percentage of the compound A of the present invention in the non-aqueous electrolyte is 0.05% to 5%. Preferably, the mass percentage of the compound A of the present invention in the non-aqueous electrolyte is 0.1 to 4%. More preferably, the mass percentage of the compound A of the present invention in the non-aqueous electrolyte is 0.5 to 2%. As an example, the mass percentage of the compound A of the present invention in the non-aqueous electrolyte is 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0024] Further, the mass percentage of the compound B of the present invention in the non-aqueous electrolyte is 0.01% to 1%. As an example, the mass percentage of the compound B of the present invention in the non-aqueous electrolyte is 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.60%, 0.70%, 0.80%, 0.90%, 1.0%, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0025] Furthermore, the lithium salt of the present invention is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bistrifluoromethylsulfonyl imide (LiTFSI), lithium bisoxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium lower aliphatic carboxylates, lithium difluorobisoxalate phosphate (LiDFBP), lithium bisfluorosulfonyl imide (LiFSI), lithium chloroborane and lithium tetraphenylborate.
[0026] Furthermore, the mass percentage of the lithium salt of the present invention in the non-aqueous electrolyte is 5-25%, preferably, the mass percentage of the lithium salt in the non-aqueous electrolyte is 8-20%, more preferably, the mass percentage of the lithium salt in the non-aqueous electrolyte is 10-15%. By way of example, the mass percentage of the lithium salt in the non-aqueous electrolyte may be, but is not limited to, 5%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 20%, 25%, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0027] Furthermore, the non-aqueous organic solvent of the present invention is selected from γ-butyrolactone (GBL), γ-valerolactone (GVL), δ-valerolactone (DVL), methyl acetate (MA), ethyl acetate (EA), ethyl propionate (EP), butyl acetate (BAC), propyl propionate (PP), butyl propionate (PRB), ethylene carbonate (EC), propylene carbonate (PCA), butylene carbonate (BC), methyl amyl carbonate, vinylene carbonate (VEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl n-propyl carbonate, The invention can be selected from at least one of ethylene glycol di-n-propyl ether (EDP), ethylene glycol di-n-butyl ether (EDB) and diethylene glycol dimethyl ether (DEGME).
[0028] Further, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte of the present invention is 65-90%, preferably, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte is 75-89%, and more preferably, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte is 78-88%. As an example, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte can be, but is not limited to, 65%, 70%, 80%, 85%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 90%, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0029] Furthermore, the non-aqueous electrolyte of the present invention also includes an auxiliary agent, which is selected from at least one of fluoroethylene carbonate (FEC), vinyl sulfite (ES), 1,3-propane sultone (PS), 1,3-propene sultone (PST), 1,4-butane sultone (1,4-BS), vinyl sulfate (DTD) and succinic anhydride (SA).
[0030] Further, the mass percentage of the additive of the present invention in the non-aqueous electrolyte is 0.05% to 5%. Preferably, the mass percentage of the additive of the present invention in the non-aqueous electrolyte is 0.1% to 4%. More preferably, the mass percentage of the additive of the present invention in the non-aqueous electrolyte is 0.5% to 2%. By way of example, the mass percentage of the additive of the present invention in the non-aqueous electrolyte is 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, but is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.
[0031] On the other hand, the present invention provides a lithium-ion battery, comprising a positive electrode material and a negative electrode material, and further comprising the above non-aqueous electrolyte.
[0032] Further, the positive electrode material is selected from at least one of nickel cobalt manganese oxide, nickel cobalt aluminum oxide, and lithium cobalt oxide. Specifically, the positive electrode material may be nickel cobalt manganese oxide, and its chemical formula may be LiNi8Co1Mn1O2, LiNi5Co2Mn3O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 or LiNi x Co y Mn z M (1xyz) O2; also, for example, the positive electrode material may be nickel cobalt aluminum oxide, and its chemical formula may be LiNi x Co y Al z N (1xyz) O2, where M and N are each independently selected from at least one of Mg, Cu, Zn, Al, Sn, B, Ga, Cr, Sr, V, and Ti, 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z ≤ 1; further, for example, the positive electrode material is lithium cobalt oxide, and its chemical formula is LiCoO2.
[0033] Further, the negative electrode material is selected from at least one of artificial graphite, natural graphite, lithium titanate, silicon-carbon composite material, and silicon monoxide. By way of example, the negative electrode material is artificial graphite, but is not limited thereto. Detailed implementation manners
[0034] To better illustrate the object, technical solution, and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the methods described in the following embodiments are further explanatory descriptions of the present invention and should not be construed as limitations on the present invention.
[0035] Example 1
[0036] (1) Preparation of non-aqueous electrolyte
[0037] In a glove box filled with argon (O2 <1ppm, H2O <1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were mixed in a weight ratio of EC:EMC:DEC=3:5:2 to obtain 85g of a non-aqueous organic solvent, followed by adding 0.5g of compound 1 and 0.01g of compound 5, dissolving and stirring well, then adding 14.5g of lithium hexafluorophosphate and mixing well to obtain a non-aqueous electrolyte.
[0038] (2) Preparation of positive electrode
[0039] NCM811, adhesive PVDF and conductive agent SuperP were mixed evenly in a mass ratio of 95:1:4 to prepare a positive electrode slurry for a lithium-ion battery with a certain viscosity. The mixed slurry was coated on both sides of an aluminum foil, and then dried and rolled to obtain a positive electrode sheet.
[0040] (3) Preparation of negative electrode
[0041] Artificial graphite, conductive agent SuperP, thickener CMC, and adhesive SBR (styrene-butadiene rubber latex) are made into slurry in a mass ratio of 95:1.5:1.0:2.5, mixed evenly, coated on both sides of copper foil with the mixed slurry, and then dried and rolled to obtain a negative electrode sheet.
[0042] (4) Preparation of lithium-ion batteries
[0043] The positive electrode, the separator and the negative electrode are wound into a soft-pack battery cell, which is packaged with a polymer aluminum-plastic film and filled with the prepared lithium-ion battery non-aqueous electrolyte. After the processes of formation and capacity separation, a lithium-ion battery with a capacity of 1000 mAh is manufactured.
[0044] The formulations of the non-aqueous electrolytes of Examples 1-20 and Comparative Examples 1-5 are shown in Table 1, wherein the steps of preparing the electrolytes and preparing the batteries of Examples 2-20 and Comparative Examples 1-5 are the same as those of Example 1.
[0045] Table 1 Formulas of non-aqueous electrolytes in various embodiments and comparative examples
[0046]
[0047]
[0048] The structural formula of compound C is shown below:
[0049] The lithium ion batteries prepared in Examples 1 to 20 and Comparative Examples 1 to 5 were subjected to high temperature cycle tests and internal resistance growth rate tests after high temperature cycles, respectively. The specific test conditions are as follows. The performance test results are shown in Table 2.
[0050] Lithium-ion battery high temperature cycle performance test
[0051] Place the lithium-ion battery in a 45℃ constant temperature box and let it stand for 30 minutes to make the lithium-ion battery reach a constant temperature. Charge it at a constant current of 1C to a voltage of 4.2V, then charge it at a constant voltage of 4.2V to a current of 0.05C, and then discharge it at a constant current of 1C to a voltage of 3.0V. Record the first discharge capacity of the battery as C0, which is a charge and discharge cycle. Then charge and discharge at 1C / 1C for 300 cycles at 45℃, record the discharge capacity as C1, and use the following formula to calculate the capacity retention rate of the lithium-ion battery.
[0052] Capacity retention rate = (C1 / C0) · 100%
[0053] Lithium-ion battery internal resistance growth rate test
[0054] Internal resistance growth rate after 300 cycles of high-temperature cycling: At 45°C, the divided battery is charged at 0.5C constant current and constant voltage at room temperature to a cut-off voltage of 4.2V, and then discharged at constant current and constant voltage until the capacity drops to 50% SOC, the internal resistance of the battery is tested, and then charged to 4.2V at 1C constant current. After 300 cycles, the internal resistance of the battery at the first full charge and the internal resistance of the battery after the last full charge are recorded.
[0055] The internal resistance growth rate of the battery after 300 cycles of high-temperature cycling = (the internal resistance of the battery after the last full charge - the internal resistance of the battery after the first full charge) / the internal resistance of the battery after the first full charge × 100%.
[0056] Table 2 Lithium-ion battery performance test results
[0057]
[0058]
[0059] Specifically, as shown in Table 2, the performance data of Examples 1 to 20 are compared with the performance data of Comparative Examples 1 to 5. It can be seen that the lithium ion batteries of Examples 1 to 20 have good high-temperature cycle performance. This may be because the additive of the present invention is an additive compound containing cyclic carbonate-sulfate and amphoteric salt. The two additives are combined. On the one hand, the solvation structure of lithium ions in the lithium ion battery is adjusted by the amphoteric salt to promote the transmission of lithium ions in the battery. On the other hand, the cyclic carbonate-sulfate undergoes a redox reaction at the positive and negative electrodes to generate long-chain CEI and SEI components rich in organic components, which helps to protect the positive and negative electrodes and slow down the side reactions with the electrolyte at high temperatures, slow down the fragmentation and pulverization of the positive electrode material particles, and reduce the growth of internal resistance. At the same time, inorganic components such as lithium carbonate and lithium sulfate in the reduction product also help the transmission of lithium ions, thereby improving the high-temperature cycle performance of the battery. Therefore, the additive is used in the non-aqueous electrolyte of the lithium ion battery, which can effectively reduce the growth of internal resistance and improve the high-temperature cycle performance of the lithium ion battery.
[0060] Further comparison of Examples 1 to 12 shows that when Compound 4 and Compound 7 are used in combination, the high temperature cycle capacity retention rate is better, which may be because the edge of Compound 4 is a DTD structure, and its end group generates a Li2DTD intermediate when the negative electrode is reduced. The intermediate can generate an inorganic SEI component of lithium sulfate, and can copolymerize with another molecule of Compound 4 or EC and other carbon-containing carbonates or sulfates to generate a higher content of lithium sulfate and a longer chain organic CS copolymer. The active intermediates generated by Compound 1 and other compounds when the negative electrode is reduced have a single reaction site. Compared with Compound 7, the generated lithium sulfate component is lower, and the copolymer has a shorter organic chain due to the difference in reaction sites. Therefore, when Compound 7 is used in combination with Compound 4, the cycle performance of the battery can be improved and the impedance growth during the cycle can be suppressed.
[0061] By comparing Examples 1 to 12 with Comparative Example 5, it can be seen that when Compound A containing cyclic carbonic acid-sulfate ester is replaced by Compound C containing only cyclic carbonate structure, its performance is poor, which may be because traditional carbon-containing organic carbonates can only form shorter chain organic oligomers, such as: LiOCOOCH2CH2O(COOCH2CH2O) n COOR or ROCOOCH2CH2O(COOCH2CH2O) nCOOR, etc. may not easily cover the inner inorganic SEI components. Some alkaline components, such as Li2CO3, are easily corroded by HF, H3PO4, etc., causing SEI film damage and causing side reactions at the interface between the electrolyte and the negative electrode. Compound A can form longer-chain organic oligomers of S=O and C=O crosses during the lithium-ion battery cycle, which cover the surface of the positive and negative electrode materials and wrap the inorganic SEI components inside the SEI layer, thereby preventing the rigid inorganic components from breaking during the charge and discharge cycle of the lithium-ion battery, causing the electrolyte to penetrate into the electrode, causing the electrolyte to decompose and fail.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A non-aqueous electrolyte comprising a lithium salt, a non-aqueous organic solvent and an additive, characterized in that: The additive comprises a compound A having a structure shown in Formula 1 and a compound B having a structure shown in Formula 2: Wherein, m and p are each independently selected from 0 or 1, X, Y, and Z are each independently selected from C or S, and X, Y, and Z are not C or S at the same time, R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C12 alkyl, substituted or unsubstituted C2-C12 alkenyl, substituted or unsubstituted C2-C12 alkynyl, and n is a natural number of 1 to 5.
2. The non-aqueous electrolyte according to claim 1, characterized in that X, Y, and Z are selected from C, one of m and p is 0 and the other is 1, X, Y, and Z are selected from S, one of m and p is 0 or 1 and the other is 1, R1 and R2 are each independently selected from hydrogen, substituted or unsubstituted C1-C6 alkyl, substituted or unsubstituted C2-C6 alkenyl, substituted or unsubstituted C2-C6 alkynyl, and n is a natural number of 1 to 5.
3. The non-aqueous electrolyte according to claim 1, characterized in that The compound A is selected from at least one of compounds 1 to 4:
4. The non-aqueous electrolyte according to claim 1, characterized in that The compound B is selected from at least one of compounds 5 to 7:
5. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage of the compound A in the non-aqueous electrolyte is 0.05% to 5%.
6. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage of the compound B in the non-aqueous electrolyte is 0.01% to 1%.
7. The non-aqueous electrolyte according to claim 1, characterized in that The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisoxalatoborate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium lower aliphatic carboxylate, lithium difluorobisoxalatophosphate, lithium bisfluorosulfonyl imide, lithium chloroborane and lithium tetraphenylborate.
8. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous organic solvent is selected from at least one of γ-butyrolactone, γ-valerolactone, δ-valerolactone, methyl acetate, ethyl acetate, ethyl propionate, butyl acetate, propyl propionate, butyl propionate, ethylene carbonate, propylene carbonate, butylene carbonate, methyl pentyl carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl n-propyl carbonate, ethyl n-propyl carbonate, propylene carbonate, 1,3-dioxolane, 1,4-dioxane, crown ether, tetrahydrofuran, 2-methyltetrahydrofuran, 2-trifluoromethyltetrahydrofuran, dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether and diethylene glycol dimethyl ether.
9. The non-aqueous electrolyte according to claim 1, characterized in that The invention also comprises an auxiliary agent, which is selected from at least one of fluoroethylene carbonate, vinyl sulfite, 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, vinyl sulfate and succinic anhydride.
10. A lithium-ion battery comprising a positive electrode material and a negative electrode material, characterized in that: It also includes the non-aqueous electrolyte according to any one of claims 1 to 9.